2018
DOI: 10.26633/rpsp.2018.167
|View full text |Cite
|
Sign up to set email alerts
|

Community acquired pneumonia incidence among children less than 5 years of age in Concordia, Argentina: vaccination impact

Abstract: Objective To measure the effectiveness of pneumococcal conjugated vaccine (PCV13) against Community Acquired Pneumonia (CAP) and invasive pneumococcal disease, 2 years after the vaccine (2+1) was included into the National Immunization Program of Argentina, and to describe variables associated with bacterial pneumonia and hospitalization. Methods This was a prospective, population-based surveillance study of CAP incidence (ambulatory and hospitalized) among children les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…When we considered these eight studies, which included age groups below 10 years of age, the median decline in radiologically confirmed pneumonia hospitalisation was 38% (range = 12% [ 33 ] to 79% [ 51 ]). Study results by age group were: for age group <12 months, median = 50% (range = 23% [ 40 ] to 53% [ 49 ]); for age group 12-23 months, median = 29% (range = 25% [ 33 ] to 70% [ 49 ]); for age group 24-59 months, median = 60% (range = 12% [ 33 ] to 79% [ 51 ]); for age group <5 years, median = 48% (range = 22% [ 40 ] to 70% [ 51 ]); and there were no vaccine impact studies for the 5-9 years age group. Four studies among age groups <12 months, 12-23 months, 24-59 months, 5-10 years, and 5-14 years showed no change.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When we considered these eight studies, which included age groups below 10 years of age, the median decline in radiologically confirmed pneumonia hospitalisation was 38% (range = 12% [ 33 ] to 79% [ 51 ]). Study results by age group were: for age group <12 months, median = 50% (range = 23% [ 40 ] to 53% [ 49 ]); for age group 12-23 months, median = 29% (range = 25% [ 33 ] to 70% [ 49 ]); for age group 24-59 months, median = 60% (range = 12% [ 33 ] to 79% [ 51 ]); for age group <5 years, median = 48% (range = 22% [ 40 ] to 70% [ 51 ]); and there were no vaccine impact studies for the 5-9 years age group. Four studies among age groups <12 months, 12-23 months, 24-59 months, 5-10 years, and 5-14 years showed no change.…”
Section: Resultsmentioning
confidence: 99%
“…Eight included studies evaluated the PCV10 or PCV13 on radiologically confirmed pneumonia hospitalisations [16,33,40,41,[48][49][50][51] (Table S6 in the Online Supplementary Document). All but two [48,50] specified that they used the WHO-defined radiologically confirmed pneumonia definition [52].…”
Section: Radiologically Confirmed Pneumonia Hospitalisationsmentioning
confidence: 99%
“…2, p. 583, 2016). Na América Latina e Caribe, estimou-se alta mortalidade por PAC em crianças, com Streptococcus pneumoniae representando a grande maioria da etiologia bacteriana desses casos (RUVINSKY et al, 2018).…”
Section: Etiologiaunclassified
“…A vacinação é uma estratégia de saúde pública muito efetiva para reduzir doenças que podem ser evitadas com vacina, com impacto na morbidade e nas internações hospitalares (RUVINSKY et al, 2018). Intervenções, incluindo medidas preventivas, como as vacinas conjugadas contra Haemophilus influenzae tipo b e pneumococo (23-valente não conjugada), e estratégias de condução terapêutica, como as diretrizes da Organização Mundial da Saúde (OMS) para o Manejo Integrado de Doenças Prevalentes na Infância (AI-DPI), causaram declínio constante na incidência e mortalidade por pneumonia (Sociedade Brasileira de Pediatria, 2021).…”
Section: Prevençãounclassified